Teacher-student relationships: An influence on the English teaching-learning process - Khairiah Syahabuddin; Rahmi Fhonna; Ulfa Maghfirah (Studies in English Language and Education, 2020)
There are two main purposes navigated in this study; first of all, it was carried out to investigate the teacher-student relationship; secondly, it was also conducted to find out whether there was a correlation between teacher-student relationship and English teaching-learning process. A number of 14 teachers and 43 students participated in this study; they are from two publish junior high schools in Aceh, Indonesia. Questionnaires for the students and interviews with the teachers were used to discover the influence of the relationship between English teachers and students, and the problems that students faced during their interactions with the teachers. There were twenty-two items in the questionnaire and five questions in the interviews that the participants needed to answer. The collected data from the questionnaire were then analysed by using a Likert scale and the Pearson product-moment correlation coefficient, meanwhile, the data from the interviews were analysed by following the stages of Miles and Huberman‘s(1994) model. In the first junior high school, a significant correlation appeared between the teacher-student relationship and teaching-learning process, with the raw score of 0.745 that refers to a high correlation. The tcount was higher than the ttable (4.784≥2.100). However, at second junior high school, had no significant correlation detected between the two variables with the raw score of 0,401 that referred to moderate correlation, where tcount was lower than ttable (2.004≤2.097). This research is expected to have a beneficial impact on the English teaching-learning process especially in the areas of the two schools, where this study took place, as well as the teachers and educators from other institutions spread in Aceh and Indonesia in general.